Solid‐Phase Synthesis of the Aged‐Nonapeptide‐Nerve‐Agent Adduct of Butyrylcholinesterase as Reference Materials for Analytical Verification. Issue 11 (14th November 2017) - Bielmann, Andreas; Curty, Christophe; Bochet, Christian G.
Abstract : Two pathways were developed and investigated for the synthesis of the 'aged'‐nonapeptide nerve‐agent bioadduct of human butyrylcholinesterase (BuChE). Considering the fast ageing of nerve‐agent adducts of BuChE in patients and biomedical samples this target molecule is of paramount relevance for quantitative analysis with respect to the Chemical Weapons Convention. Two approaches using a precursor bearing a hydroxyl on its phosphonyl moiety and a benzyl protected precursor were considered. Several impurities were identified and circumvented during the optimization of the peptide synthesis step. The 'aged'‐nonapeptide adduct was successfully synthesized by solid‐phase‐peptide‐synthesis (SPPS). Abstract :